The Role of Religious Norms On Selecting The Islamic Bank - Hardius Usman (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
The aims of this study are to examine Muslim’s religious norms regarding to their belief on  the  law  of  the  prohibition  of  bank  interest,  and  to  investigate  the  effect  of religius norms on customers’ decision in using the Islamic banking services. This study employs natural experimental design with Analysis of Variance (ANOVA), and Pearson Chi-Square Test. The exploratory study also conducted to support the quantitative analysis. The results show that the religious norms among Muslims classified into two categories, i.e: traditional and contemporary group and the religious norm of the Muslim have significant affects on the decision in using the Islamic banks.DOI:10.15408/aiq.v7i1.1356